Nomenclature and typification in Polyosma (Escalloniaceae) from New Caledonia, with the description of a new species - Pillon, Yohan (Phytotaxa, 2018)
The taxonomy of Polyosma (Escalloniaceae) in New Caledonia is reviewed. All names validly published in Polyosma in this archipelago are discussed and lectotypified when necessary and possible. A new combination is made, Polyosma subintegrifolia; and a new species, Polyosma kouaouana, is described. Seven species (all endemic) are recognized in New Caledonia: P. brachystachys, P. discolor, P. kouaouana, P. leratii, P. pancheriana, P. spicata, and P. subintegrifolia. A preliminary identification key is provided.